Cortical nicotinic enhancement of tone-evoked heightened activities and subcortical nicotinic enlargement of activated areas in mouse auditory cortex. (August 2022) - Nakanishi, Makoto; Nemoto, Masahito; Kawai, Hideki Derek
Abstract: Systemic nicotine administration regulates neuronal activities in mouse auditory cortex. How nicotine regulates the spread of the activities across auditory cortical areas is not well known. We investigate this using flavoprotein fluorescence imaging. 20 kHz amplitude-modulated (AM) tones increased the peak intensity of flavoprotein fluorescence in presumptive primary auditory cortex (A1). 5 kHz AM tones activated at least three cortical areas, which are presumably A1, anterior auditory field, and secondary auditory cortex. Nicotine enlarged tone-activated cortical areas and enhanced both 20 kHz and 5 kHz tone-evoked fluorescence intensities at their respective, optimal frequency peak sites and at non-optimal frequency peak sites in A1. The extent of this enhancement was greater at non-optimal frequency sites than at optimal frequency sites. A cortical injection of dihydro-β-erythroidine, an inhibitor of nicotinic acetylcholine receptors composed of α4 and β2-subunits (α4β2*-nAChRs), blocked the enhancement of fluorescence intensity at the peak sites but did not appear to block the enlargement of activated areas. These results suggest that nicotine exposure activates cortical α4β2*-nAChRs to enhance tone-evoked local neuronal activities at an optimal frequency site. The nicotine-induced enlargement of a tone-activated area may depend on the nicotinic enhancement of cortical inputs or other activities. Highlights: Nicotine exposure enhanced tone-evoked flavoprotein fluorescence via α4β2*-nAChRs. Nicotine enlarged activated cortical areas independent of cortical nAChRs. Nicotinic increase of peak intensity and activated area lasted at least 25 min. Nicotine did not suppress flavoprotein responses at non-optimal frequency sites. Nicotine enhanced tone-evoked responses in anterior and secondary auditory fields.